The prevalence of depression among secondary school students of Kuantan, Pahang, Malaysia. - Mohamed, Mossad Abdelhak Shaban; Abd Rahman, Siti Zubaidah; Zakaria, Rozanizam; Abubakr, Asrar; Anuar, Muhamad Azamin; Abd Latif, Siti Norsyazwani (2019)
Introduction: Depression is a curable debilitating illness that becomes a leading cause of morbidity and mortality globally. The prevalence of depression is underrecognized among adolescents. The study is conducted to determine the prevalence of depression among secondary school students of Kuantan Malaysia. Materials and method: We conduct a quantitative cross-sectional study. A population of 414 students from two urban schools, two rural schools, and one international school will participate in the study. The assessment tool used is the Malaysian version of Depression, Anxiety and Stress Scale 21 (DASS 21). Data will be analyzed using SPSS version 21 (SPSS IBM, New York, USA). Factors associated with depressive symptoms will be analyzed using multi Variate logistic regression analysis. Results: Prevalence of depression in Kuantan, Malaysia will be compared to the same international trends. Conclusion: Our study can determine and compare the prevalence of depression in different categories. Education and early interventions of depressed adolescents will add extra value of the project